Global, regional, and national burden and trends of rheumatoid arthritis among the elderly population: an analysis based on the 2021 Global Burden of Disease study - Wei, Lu; Chen, Xiang; Liu, Mengmeng (Frontiers in Immunology, 2025)
BackgroundRheumatoid arthritis (RA) is an autoimmune and inflammatory disease. In elderly patients, the disease progresses more rapidly, involves more complications, and places a greater burden on health. Currently, there is a lack of studies investigating the disease burden of RA in the elderly population.MethodsWe analyzed data on elderly rheumatoid arthritis from the Global Burden of Disease (GBD) database for 1990–2021, focusing on three main indicators: prevalence, incidence, and Disability-Adjusted Life Years (DALYs). Percentage change and the estimated annual percentage change (EAPC) were used to evaluate the trends in the disease burden.ResultsIn 2021, the global prevalence cases, incidence cases, and DALYs of elderly RA were 7,919,136, 334,291, and 1,549,877, representing increases of 157.59%, 169.71%, and 116.53% compared to 1990. Both the prevalence rate and incidence rate increased, with EAPCs of 0.54 (95% CI: 0.5, 0.58) and 0.75 (95% CI: 0.7, 0.79), respectively. Notably, the prevalence rate in females was 2.2 times higher than that in males. The DALY rate showed a slight decline. Among the five Socio-demographic Index (SDI) regions, the High SDI region had the highest prevalence cases, incidence cases, and DALYs in 2021, with 2,821,305, 114,994, and 483,579, respectively, accounting for 36%, 34%, and 32% of the global totals. This region also recorded the highest prevalence and incidence rates. In contrast, the Low SDI and Low-middle SDI regions exhibited the fastest growth in both prevalence and incidence cases as well as rates. The highest prevalence cases and incidence rate were observed in the 65–69 age group. Decomposition analysis revealed that the rising disease burden was primarily attributable to the growth of the global elderly population.ConclusionsBetween 1990 and 2021, the global burden of rheumatoid arthritis in the elderly population increased. The High SDI region experienced the highest disease burden. In contrast, the Low and Low-middle SDI regions showed the most rapid growth in disease burden. Females exhibited a higher burden compared to males, with the highest burden observed in the 65–69 age group. Early diagnosis and treatment in elderly patients are essential to mitigating adverse outcomes and reducing the burden.